Implementasi Sepuluh Amal Lahiriyah Perspektif Imam Alghazali dalam Pembentukan Habitus Religius Santri: (Studi tentang Strategi Preventif Pesantren terhadap Kecenderungan Akhlak Madzmumah di Pondok Pesantren Banuraja 2026) - Endang Komara; Ahmad Sukandar; Badrul Munir (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Adolescents in the digital era encounter complex moral and spiritual challenges, requiring educational approaches that integrate religious knowledge with sustainable character formation. This study explores the implementation of Imam Al-Ghazali’s concept of the Ten External Deeds (Sepuluh Amal Lahiriyah) among Madrasah Aliyah students at Pondok Pesantren Banuraja as a foundation for developing religious habitus and strengthening moral character. Using a qualitative descriptive approach, data were collected through participant observation, semi-structured interviews, Focus Group Discussions (FGDs), and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with credibility maintained through triangulation, member checking, and prolonged observation. The findings indicate that the Ten External Deeds have been systematically implemented through daily habituation, exemplary leadership, mentoring, collective religious activities, and the Manhaj Attahqiq Albidayah spiritual tradition. These practices cultivate stable religious habits, including congregational prayer, Qur’anic recitation, dhikr, charity, voluntary fasting, social responsibility, amar ma’ruf nahi munkar, and adherence to the Sunnah. The study concludes that the pesantren environment serves as an effective preventive educational ecosystem that strengthens self-control, spiritual awareness, social responsibility, and moral resilience. This model offers valuable insights for developing Islamic character education based on Imam Al-Ghazali’s educational philosophy.